CONSTRUCTION OF LOW COST SPIN AND DIP COATERS FOR THIN FILM DEPOSITION USING OPEN SOURCE TECHNOLOGY (2014)
A novel low cost method was developed for the construction of a spincoater and a dip coater device incorporating inexpensive mechanicalcomponents and open-source software. Both devices are utilized fordepositing thin films, and can be built with interdisciplinaryknowledge of physics, mechanics, and electronics at the undergraduate level. The spin coater permits a wide speed range (from 500 to 10,000 rpm), and the velocity range of the dip coater stretches (from 0.6 cm/h to 30 cm/min). The operational parameters of these instruments compare favorably with commercial models.